Влияние условий получения гидроксидов и оксидов алюминия на спекание и свойства керамики - А. А. Ханамирова (ՀՀ ԳԱԱ հրատ.)
Рассмотрены различные методы получения корунда в виде ультрадисперсных порошков. Систематизирована и обсуждена информация о свойствах корунда и корундовой керамики. Դիտարկվել են գերդիսպերսային փոշիների ձևով կորունդի ստացման տարբեր եղանակները: Համակարգավորված ու քննարկված է կորունդի և կորունդային խեցեղենի հատկությունների մասին ինֆորմացիան: Under the conditions of the science- and engineering progress the role of corundum and corundum ceramics possessing a whole complex of valuable properties – thermoresistance, high mechanical strength, high electroinsulation capability, resistant properties, corrosion stability and many other properties – is constantly increasing.
Keywords: Science; Chemistry